Information systems strategic planning in multinational corporations: from subsidiaries' perspective - Mohdzain, Mohdzaher (Cranfield University, 2003)
This thesis examined information systems strategic planning in multinationals from the perspective of the subsidiaries. A research framework was synthesised from a combination of literature in the fields of multinational strategy and IS strategic planning. The research was carried out using multiple case studies involving eight multinational subsidiaries operating in Malaysia and a multinational subsidiary operating in the UK. The subsidiaries were units in four European-based, three US-based, and two Japanese-based multinationals. The main methods and instruments used for the study were site visits and semistructured interviews. Three corporate headquarters were visited, in Switzerland, the US, and The Netherlands and a telephone interview was held with another corporate IT interviewee based in the US. The evidence gathered from the case studies reveals that, in these organisations, there is a lack of alignment between IS and business strategy. IS planning is more tactical rather than strategic and is more dominated by the IT infrastructure rather than the IS portfolio. The main focus of IS planning in many of these companies is to control cost and achieve scale economies, while knowledge transfer and subsidiary initiative get less priority. IS planning in these companies is centralised or currently moving toward more centralisation. Project implementation was the main criterion used for measuring IS planning success. With a low level of involvement of the local business management in the IS planning, in general, the subsidiary business managers are less satisfied with the IS planning approach than the subsidiary IT managers. Analysis of the evidence gathered from the case studies also indicates that there are links between business orientation, IS planning orientation, IS planning approaches, and the perceived success of IS planning. Small subsidiaries also tend to have less autonomy in IS planning and IS managers who report to the financial controllers tend to be less satisfied with the IS planning approach.